Analisa Pengaruh Bulbous Bow terhadap Tahanan Kapal dan Konsumsi Bahan Bakar pada Kapal Perintis 2000 GT - Maruto Prijono Agil; Antoko Bambang; Gafur Abdul (Politeknik Perkapalan Negeri Surabaya, 2018)
One to improve the performance of the ship is change the optimal shape of bow and stern, so thatship resistance can be reduced. Many studies discuss innovations hull shape in order to get the optimaldesign, in order to obtain the hull shape especially the bow shape that has the smallest value of totalresistance. Therefore, this study will discuss the design of the bulbous bow at coaster ship 2000 GT withsome variety of bulbous bow shape and calculation of resistance and fuel consumption aimed to obtainingthe bow shape with the smallest total resistance value and efficient fuel consumption. 3D modeling of bowand calculation of ship resistance using Maxsurf Software. Variations of bulbous bow design that have beenmodeled there are 3 models of bulbous bow type Î”, bulbous bow type O, and bulbous bow type V. Theresults of the resistance calculation on the coaster ship 2000 GT without bulbous bow using the maxsurfsoftware obtained for 186.6 kN, ship resistance value on bulbous bow shape Î” obtained 144.4 kN, andvariation of bulbous bow type V has the highest ship resistance value of 153.9 kN. Furthermore, thecalculation of fuel consumption on the coaster ship 2000 GT obtained results of 49.884 tons, variation ofbulbous bow type Î” of 40,79 tons, variations of type O bulbous bow of 42.79 tons, and variation of bulbousbow type V at 45.86 tons.